The spillover effects of a bright-line regulation: evidence from China. Issue 1 (8th January 2020) - Song, Yunling; Li, Shihong; Zhou, Ling
Abstract : Purpose: The purpose of this paper is to investigate the spillover effects of a bright-line disclosure regulation that required Chinese listed firms to provide earnings forecasts if they anticipated specified, large earnings changes. Design/methodology/approach: The paper examines the discontinuity of the earnings change distribution of firms listed on the Shenzhen Stock Market between 2010 and 2014. The paper finds that firms no longer subject to the bright-line test still exhibited discontinuity in earnings change distribution. The discontinuity lasted for at least three years with magnitude comparable to that of the firms still subject to the bright-line test. In addition, newly listed firms that had never experienced the bright-line test showed similar tendency to avoid the same threshold. There is some evidence that these firms' avoidance of the −50 per cent changes was partly because of market pressure. Research limitations/implications: Research on bright-line tests has to date focused on their immediate and direct effects on firms currently subject to such tests. This study finds that a bright-line disclosure regulation's influence is not limited to the firms directly governed by the regulation. It could lead to widespread and long lasting distortions in financial reporting behaviors of firms not currently subject to such tests. Practical implications: The paper has implications for regulators who study the economic consequences of bright-line regulations in general and analysts of the Chinese capital market in particular. Originality/value: This is the first empirical report that bright-line disclosure regulations affected the financial reporting behavior of firms that were not directly subject to the bright-line tests.